Effect of intravenous morphine comedication on bile duct visualization, diameter and volume applying intravenous CT cholangiography in a porcine liver model - Sommer, Christof-Matthias; Schwarzwälder, Christoph Bernhard; Bellemann, Nadine; Stampfl, Ulrike; Stiller, Wolfram; Schindera, S.T.; Omri, Wafa; Nickel, Felix; Gehrig, Tobias; Kenngott, Hannes Götz; Richter, Götz Martin; Meinzer, Hans-Peter; et al. (European surgical research, 2010)
Background/Aims: To determine whether intravenous morphine comedication improves bile duct visualization, diameter and/or volume applying intravenous CT cholangiography in a porcine liver model. Methods: 12 Landrace pigs underwent intravenous CT cholangiography. Eight minutes after initiation of the contrast material infusion, either morphine sulfate (n = 6 animals) or normal saline (n = 6 animals) was administered. Eighteen consecutive CT scans of the liver were acquired with 2-min intervals starting with initiation of the contrast material infusion. Maximum bile duct visualization scores, diameters and volumes and time to maximum bile duct visualization scores, diameters and volumes were determined. Results: Maximum bile duct visualization scores, diameters and volumes and time to maximum bile duct visualization scores, diameters and volumes were not significantly different when the morphine group was compared to the normal saline group. Maximum bile duct visualization scores ranged between 4.00 ± 0.00 and 2.83 ± 1.47. Maximum bile duct diameters ranged between 6.77 ± 0.40 and 2.10 ± 1.35 mm. Maximum bile duct volume was 16.41 ± 7.33 ml in the morphine group and 16.79 ± 5.65 ml in the normal saline group. Conclusion: Intravenous morphine comedication failed to improve bile duct visualization and to increase bile duct diameter and volume applying CT cholangiography.
Gesehen am 15.08.2023